Pengaruh Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variable Intervening pada Pelanggan Pusat Kebugaran New Body - Saiyaf Fakhri Aprilio; Lukman Hadi; Agus Nurudin (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study investigates the effect of service quality and price on customer loyalty with customer satisfaction as an intervening variable to New Body customers fitness center. With the fitness market gaining more and more competition, knowing what drives customer loyalty is a must. The method applied for this research is Structural Equation Modeling (SEM), and based on 221 respondents who are customers of New Body as the data collection technique through questionnaires. The result shows that there is a positive and significant effect of customer satisfaction on customer loyalty. In another finding, service quality has an insignificant negative effect on loyalty, but in the presence of customer satisfaction as an intervening variable, its effect is positive. Price also affects loyalty as the direct effect of price on loyalty is high. Our findings provide suggestions for marketing strategies of fitness centers aimed at improving service quality to be in line with expectations create satisfaction and therefore enhance loyalty toward the fitness center